Oxygen Vacancy‐Induced Topological Hall Effect in a Nonmagnetic Band Insulator. Issue 7 (27th May 2020) - Ojha, Shashank Kumar; Gogoi, Sanat Kumar; Patidar, Manju Mishra; Patel, Ranjan Kumar; Mandal, Prithwijit; Kumar, Siddharth; Venkatesh, Radhakrishnan; Ganesan, Vedachalaiyer; Jain, Manish; Middey, Srimanta
Abstract: The discovery of skyrmions has recently sparked tremendous interest in topologically nontrivial spin textures. The signature of the noncoplanar nature of magnetic moments can be observed as topological Hall effect (THE) in electrical measurement. Realization of such nontrivial spin textures in new materials and through new routes is an ongoing endeavor due to their huge potential for future ultra‐dense, low‐power memory applications. In this work, oxygen vacancy (OV)‐induced THE and anomalous Hall effect (AHE) in a 5 d 0 system KTaO3 are reported. The observation of weak antilocalization behavior and THE in the same temperature range strongly implies the crucial role of spin–orbit coupling (SOC) behind the origin of THE. Ab initio calculations reveal the formation of the magnetic moment on Ta atoms around the OV and Rashba‐type spin texturing of conduction electrons. In the presence of Rashba SOC, the local moments around vacancy can form bound magnetic polarons (BMPs) with noncollinear spin texture, resulting in THE. Scaling analysis between transverse and longitudinal resistance establishes skew scattering‐driven AHE in the present case. This study opens a route to realize topological phenomena through defect engineering. Abstract : Magnetic materials with nontrivial spin textures show huge prospects for future ultra‐dense, low‐power memory applications. The sign of the noncoplanar nature of magnetic moments in such systems can be observed as topological Hall effect in electrical measurement. In this work, a new route is demonstrated to realize topological Hall effect in a nonmagnetic system KTaO3 through oxygen vacancy creation.